2002
DOI: 10.1021/jp013729i
|View full text |Cite
|
Sign up to set email alerts
|

Unique Performance and Characterization of a Crystalline SbRe2O6Catalyst for Selective Ammoxidation of Isobutane

Abstract: The catalytic performances of a new family of crystalline Re-Sb-O compounds SbRe 2 O 6 , SbOReO 4 ‚2H 2 O and Sb 4 Re 2 O 13 in selective ammoxidation of isobutane (i-C 4 H 10 ) to methacrylonitrile (MAN) have been studied and compared with those of a mechanical mixture of Sb 2 O 3 + Re 2 O 7 , coprecipitated SbRe 2 O x , Sb 2 O 3 -supported Re 2 O 7 , bulk Re oxides, and Sb oxides. SbRe 2 O 6 efficiently catalyzed the i-C 4 H 10 ammoxidation to MAN at 673 K with the good selectivity to MAN (44.9%) and to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Antimony has been widely used as a key component in many selective oxidation catalysts, including V-Sb-O [1][2][3][4][5], MoSb-O [6,7], Fe-Sb-O [8,9], Sn-Sb-O [10,11], V-Sb-Ni-O [12], Re-Sb-O [13]. Excess antimony of antimony-containing mixed oxide catalysts has been found to be a clue to high selectivity to partially oxidized products [14].…”
Section: Introductionmentioning
confidence: 99%
“…Antimony has been widely used as a key component in many selective oxidation catalysts, including V-Sb-O [1][2][3][4][5], MoSb-O [6,7], Fe-Sb-O [8,9], Sn-Sb-O [10,11], V-Sb-Ni-O [12], Re-Sb-O [13]. Excess antimony of antimony-containing mixed oxide catalysts has been found to be a clue to high selectivity to partially oxidized products [14].…”
Section: Introductionmentioning
confidence: 99%
“…Antimony is widely used as a key element in mixed oxide catalysts for selective oxidation of hydrocarbons, such as Fe−Sb−O, Sn−Sb−O, V−Sb−O, , Mo−Sb−O, and Re−Sb−O. Many studies on the mixed oxides except for Re−Sb−O have demonstrated that excess antimony at surfaces is a clue to high selectivity to partially oxidized products. Allen and Bowker investigated propene oxidation on FeSbO 4 catalysts and reported that the catalyst surfaces were covered by antimony rich thin layers under the selective oxidation conditions .…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Antimony trioxide (Sb 2 O 3 ) is a transparent material with an indirect band gap of 3.3 eV and has been widely used in fields of catalysis, fire retardants, glasses, sensors, as anode material for the Li-ion batteries, and retardants for rubber, ceramics, enamels, fabrics, and fiber products [1][2][3][4][5][6][7]. Moreover, the Sb 2 O 3 thin film behaves as an n-type semiconductor [8], which invites its photovoltaic applications.…”
mentioning
confidence: 99%